STREET AND ROAD NETWORK’S PLANNING PRINCIPLES FOR NEEDS OF PERSONS WITH DISABILITIES (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
The development and improvement problem of principles and receptions of streettravellingnetwork planning and also facilities of their providing, that would take into accountthe necessities of all users an environment, is in-process investigated, especially people withdifferent disability nosologies and other categories of people with limited mobility.Distinguished basic groups of principles in relation to planning of environment. Analysedbasic principles of planning of street-travelling network for conditioning for unimpeded motionby the community of all participants of traffic participants: functional integration, functionaldifferentiation, compactness, town-planning integrating, microdistricts creation, constructionof optimal street-travelling network, functional zoning, non-conflictual, modernisation,aesthetic attractiveness, visual perception, sequentialization, design of spatial corridor,universal design, availability, comfort, informing, unconcern, «smart adaptation», social,social adaptation, participating in public life, labour employment.Keywords: street and road network, people with limited mobility (PLM), transportaccessibility, mobility, transport infrastructure, design principles.